2016
DOI: 10.1002/erv.2433
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Psychosocial Predictors of Onset and Cessation of Eating Pathology amongst College Women

Abstract: The course of college women's eating pathology is variable. Little is known about psychosocial factors prospectively predicting maintenance/cessation or the new onset of clinically significant disordered eating symptoms. This study aimed to address these research gaps. College women (N = 2202) completed an assessment of eating pathology and potential risk/maintenance factors at two time points, 9 months apart. Logistic regression models indicated that elevated body dissatisfaction, thin-ideal internalization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
39
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 33 publications
9
39
3
2
Order By: Relevance
“…maladjustment and illness-specific functional impairment (medium-to-large effect sizes), with significantly higher levels/rates across the severity groups. Ambwani et al, 2015;Dakanalis, Carrà, Calogero et al, 2015a;Dakanalis, Clerici et al, 2016b;Dakanalis, Favagrossa et al, 2015e;Dakanalis, Timko et al, 2016d;Dakanalis, Zanetti, Riva, & Clerici, 2013a;Haedt-Matt & Keel, 2011;Ivanova et al, 2015;Lampard et al, 2013). They are also consistent with earlier research indicating that more frequent BE was related to greater ED, general and comorbid psychopathology, higher mean BMI and prevalence of determinants of the MetSyn (hypertension, hyperglycemia and dyslipidemia) and lower psychosocial functioning (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…maladjustment and illness-specific functional impairment (medium-to-large effect sizes), with significantly higher levels/rates across the severity groups. Ambwani et al, 2015;Dakanalis, Carrà, Calogero et al, 2015a;Dakanalis, Clerici et al, 2016b;Dakanalis, Favagrossa et al, 2015e;Dakanalis, Timko et al, 2016d;Dakanalis, Zanetti, Riva, & Clerici, 2013a;Haedt-Matt & Keel, 2011;Ivanova et al, 2015;Lampard et al, 2013). They are also consistent with earlier research indicating that more frequent BE was related to greater ED, general and comorbid psychopathology, higher mean BMI and prevalence of determinants of the MetSyn (hypertension, hyperglycemia and dyslipidemia) and lower psychosocial functioning (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…This goes against the traditional views and previous literature [15, 16, 18], which expect women who objectify themselves to have symptoms of eating disorders. This result could be explained by the fact that the majority of the respondents were from a Muslim orientation.…”
Section: Discussionmentioning
confidence: 49%
“…Although conducted independently, the study by McKinley and Hyde [14] offers an indirect explanation for the relationship between self-objectification, body shame, and disordered eating that was previously explained by the objectification theory. In studies conducted by Dakanalis et al [15, 16], it was found that self-objectification was the biggest contributing factor towards eating disorders amongst young women, over other variables such as ideal internalization, body dissatisfaction, dieting, and negative affectivity. Sinclair [17] investigated the relationship between objectification experiences, sociocultural attitudes towards appearance, and objectified body consciousness.…”
Section: Introductionmentioning
confidence: 99%
“…Diferentes factores influyen en la aparición de esta patología; entre los cuales se citan los factores culturales, las influencias de los medios de comunicación, familiares, hereditarios, el acoso de sus pares, padres y hermanos, factores temporales de fracasos y conflictos personales, y los factores de vulnerabilidad personal en el que el individuo no se acepta a sí mismo como una persona diferente del (15)(16)(17)(18)(19)(20) resto por problemas de autoestima .…”
Section: Discussionunclassified